Self-perception and popular practices of oral health among black slave descendants elderly women in Brazil - Maria Fernanda Neves Silveira de Souza; Luiza Fernandes Fonseca Sandes; Amanda Miranda Brito Araújo; Daniel Antunes Freitas (Sociedade Brasileira de Medicina de Família e Comunidade, 2018)
Objective: To investigate the perception and oral health practices among older quilombola women (black population group, descendants of slaves in Brazil). Methods: Qualitative research with elderly women living in a rural community formed by descendants of slaves in Brazil. The study was performed through a semi-structured interview with nine of the rural community residents and following content analysis of the narratives. Results: All elderly women are edentulous (partially or totally) and dental problems that led them to use natural means of pain relief were identified. With the analysis of the transcripts, three main categories emerged: the elderly of Quilombola Rural Community Julia Mulata and edentulism; self-perceived oral health of older women of the Quilombola Rural Community Julia Mulata; Popular practices used in the presence of health problems. Conclusion: Quilombola elderly consider the loss of teeth as natural aging; they present life stories linked to dental problems; seek to solve their dental problems with the use of traditional folk therapies.